Reactive nitrogen, ozone, and nitrate aerosols observed in the Arctic stratosphere in January 1990 - Kondo, Y.; Aimedieu, P.; Koike, M.; Iwasaka, Y.; Newman, P. A.; Schmidt, U.; Matthews, W. A.; Hayashi, M.; Sheldon, W. R. (1992)
Ozone mixing ratios in the vicinity of the 525-K potential temperature surface in January and early February of 1990 were observed to decrease sharply across the edge of the vortex boundary, where the vortex position was estimated from Ertel's potential vorticity. The changes in NO(y) mixing ratio with respect to altitude measured on January 18 and 31 were quite well correlated with those of ozone between 15 and 24 km, indicating that NO(y) also had a large gradient across the edge of the vortex. This is interpreted as being mainly due to the significant denitrification that occurred inside the vortex. The total amount of gas and particulate phase HNO3 was close to the NO(y) amount at the altitude of the 22- to 23-km region, suggesting that the conversion of non-HNO3 reactive nitrogen to HNO3 had occurred with a PSC.